2018
DOI: 10.1061/(asce)mt.1943-5533.0002515
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Linear Viscoelastic Properties of Two Bituminous Mixtures Made with the Same Binder

Abstract: Eiffage developed a high-performance bituminous mixture known as GB5. It is based on aggregate optimization method. This paper presents the results of a research project checking whether, in the small strain domain, this type of mixture behaves like the more conventional asphalt mixture GB3 currently used as a base layer in French bituminous pavements. Three-dimensional complex modulus tests are performed on GB5 and GB3, two hot mixtures asphalt (HMA) made with the same bitumen but produced with different aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Mortars with higher aggregate content and/or including air voids, however, can also be understood through the packing-concept, similar to an asphalt concrete with small aggregates, and thus could not be considered incompressible. In several recent studies, Poisson's ratio of bitumen and bitumen aggregate mixtures were shown to be dependent on temperature and load time / loading frequency (Alanazi, Kassem, Grasley, & Bayomy, 2017;Benedetto, Delaporte, & Sauzéat, 2007;Gudmarsson, Ryden, Di Benedetto, & Sauzéat, 2015;Perraton, Di Benedetto, Sauzéat, Nguyen, & Pouget, 2018). In particular, (Benedetto et al, 2007) reports measured Poisson's ratios at 0°C for bitumen and bitumen-filler mastics with 32% filler volume concentration, to be close to 0.5 at low loading frequencies and decrease to approximately 0.48 at loading frequency of 5 Hz.…”
Section: Problem Formulation and Computational Studymentioning
confidence: 98%
See 1 more Smart Citation
“…Mortars with higher aggregate content and/or including air voids, however, can also be understood through the packing-concept, similar to an asphalt concrete with small aggregates, and thus could not be considered incompressible. In several recent studies, Poisson's ratio of bitumen and bitumen aggregate mixtures were shown to be dependent on temperature and load time / loading frequency (Alanazi, Kassem, Grasley, & Bayomy, 2017;Benedetto, Delaporte, & Sauzéat, 2007;Gudmarsson, Ryden, Di Benedetto, & Sauzéat, 2015;Perraton, Di Benedetto, Sauzéat, Nguyen, & Pouget, 2018). In particular, (Benedetto et al, 2007) reports measured Poisson's ratios at 0°C for bitumen and bitumen-filler mastics with 32% filler volume concentration, to be close to 0.5 at low loading frequencies and decrease to approximately 0.48 at loading frequency of 5 Hz.…”
Section: Problem Formulation and Computational Studymentioning
confidence: 98%
“…For a hot mix asphalt (HMA) time and temperature dependence of Poisson's ratio is reported to be more profound; e.g. (Perraton et al, 2018) measured for HMA with 4.5% binder content by weight υ(t) varying from approximately 0.25 to 0.47 at 0°C.…”
Section: Problem Formulation and Computational Studymentioning
confidence: 99%
“…This indicates that the SBS-modified asphalt mixture requires more energy than the PU mixture to shift data points to the reference temperature across all test temperatures. Several studies have shown that shift factor α r is influenced by the bitumen, with different asphalt mixtures using the same bitumen exhibiting the same shift factor, α r [6,7,85]. Therefore, this difference can be attributed to the significant difference in the properties of the SBS-modified asphalt and PU binder, which could impact the LVE property of their respective mixtures.…”
Section: Comparison Of Shift Factorsmentioning
confidence: 99%
“…These two parameters can be 37 determined by applying sinusoidal cyclic loadings on the tested specimens in small 38 strain domain. Within LVE domain, many authors confirmed that the Time 39 Temperature Superposition Principle (TTSP) can be applied as a good approximation 40 for bituminous materials [5][6][7][8][9][10][11]. In addition, the behaviour of bituminous materials 41 can be modelled using the linear viscoelastic theory.…”
Section: Introductionmentioning
confidence: 99%